2001
DOI: 10.1016/s0735-1097(01)01288-8
|View full text |Cite
|
Sign up to set email alerts
|

Physician-performed point-of-care echocardiography using a laptop platform compared with physical examination in the cardiovascular patient

Abstract: Point-of-care echocardiography using a miniaturized echocardiographic platform substantially improved the detection of important cardiovascular pathology compared with PE. Use of this device by a cardiovascular specialist with training in echocardiography as a routine adjunct to PE appears to be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
104
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(112 citation statements)
references
References 14 publications
8
104
0
Order By: Relevance
“…However, barriers to the widespread implementation of an echocardiographic method in outpatient dialysis clinics include the cost and availability of conventional ultrasound machines, as well as the specialized training that is necessary for operation of these platforms. The introduction of hand-carried cardiac ultrasound (HCU) devices, which are relatively inexpensive and portable, has allowed bedside cardiac evaluation at the time of physician encounter in numerous settings (25)(26)(27). Recent studies have demonstrated acceptable accuracy when limited HCU examinations were performed by noncardiologists (28,29).…”
mentioning
confidence: 99%
“…However, barriers to the widespread implementation of an echocardiographic method in outpatient dialysis clinics include the cost and availability of conventional ultrasound machines, as well as the specialized training that is necessary for operation of these platforms. The introduction of hand-carried cardiac ultrasound (HCU) devices, which are relatively inexpensive and portable, has allowed bedside cardiac evaluation at the time of physician encounter in numerous settings (25)(26)(27). Recent studies have demonstrated acceptable accuracy when limited HCU examinations were performed by noncardiologists (28,29).…”
mentioning
confidence: 99%
“…Several previous studies reported that HCU showed good concordance of diagnostic capability with SED in terms of assessing LVEF and LV dimension measurement and detecting pericardial effusion and valve disease (4)(5)(6)(7)(8)(9) . Also, they are being placed in emergency or critical care settings to assist in the evaluation of hemodynamically compromised patients (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 86%
“…With the currently available hand-held echocardiography equipment a trained physician is able to detect cardiac pathology with high sensitivity. 29 The relatively high number of patients with diastolic dysfunction could be explained by the high percentage of patients with hypertension. The prevalence of hypertension was comparable with the prevalence of hypertension in non-Hispanic white men in the NHAHES survey.…”
Section: Discussionmentioning
confidence: 99%